Pengaruh Model Pembelajaran Student Team Achievement Divisions (STAD) terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Sabrun, Sabrun (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2021)
This study aims to determine the effect of the Student Team Achievement Divisions (STAD) learning model on students' mathematical problem solving abilities, student activities, and to see the implementation of the Student Team Achievement Divisions (STAD) learning model on cube and block material for class VIII SMP Negeri 2 Narmada. This research is a quantitative research with experimental methods and uses a Pre-Experimental design in the form of Posttest-Only Control Design. The population in this study were all class VIII SMP Negeri 2 Narmada which consisted of five classes totaling 186 students. Samples were taken by simple random sampling technique. The sample consists of two classes, namely class VIIID as an experimental class with 35 students and class VIIIE as a control class with 35 students. The test results obtained a reliability level of 0.88 with a total of 28 students. It can be interpreted that the students' mathematical problem solving ability test questions have very high reliability and are suitable for use. The analysis carried out in this study was to determine the effect of the Student Team Achievement Divisions (STAD) learning model on students' mathematical problem solving abilities using the t-test calculation where the results of the analysis showed the influence of the Student Team Achievement Divisions (STAD) learning model on mathematical problem solving abilities. students of 0.91 with strong criteria. Analysis of student learning activity observation sheets showed an increase in student learning activities, which in the first meeting obtained a percentage of 87.15% and the second meeting was 89.11% with very active criteria. Analysis of the observation sheet on the implementation of the Student Team Achievement Divisions (STAD) learning model using the calculation of the percentage of implementation frequency obtained the percentage of 81.91% very good criteria.